Developing teaching materials of natural product chemistry to ıncrease student’s life skills - Tukiran; Suyatno; Hıdayatı, Nurul (Journal of Turkish Science Education, 2017)
The research aimed to develop teaching materials of natural product chemistry (NPC) by conducting group investigation of cooperative learning model to increase students’ life skills and to describe their feasibility. In this research, students’ life skills include academic and social skills. Then, the intended feasibility includes three aspects—validity, practicality, and effectiveness aspect. The teaching materials (i.e., syllabus, lesson plan, students’ books, and students’ worksheets) accompanied by students’ life skills observation sheets were developed using Research & Development methods as proposed by Borg and Gall. The teaching materials developed were used for the students of Chemistry Department, Universitas Negeri Surabaya, Indonesia. The developed materials were further assessed and validated by an expert (for validity aspect), and the implementation of the materials in the class were observed by a number of observers (for practicality and effectiveness aspects) and then analyzed quantitatively and described qualitatively. The findings of the research showed that the developed teaching materials of NPC were feasible because of their validity, practicality, and effectiveness. This means that the materials were valid according to the expert’s judgments, were practical and effective when implemented in the NPC learning process, and were able to increase students’ life skills.
Keywords: Feasibility; Natural Product Chemistry; Students’ Life skills; Teaching Materials